THE ESSENCE OF SOCIAL SECURITY SYSTEM IN POLAND - Elżbieta A. Maj (Zeszyty Naukowe Wyższej Szkoły Finansów i Prawa w Bielsku-Białej, 2015)
The article discusses the Polish social security system and includes the analysis of three areas: social security system, social provisions and social assistance. Special attention is paid to basic characteristics of these systems and the normative basis for their actions. The author uses the following methods: dogmatic – legal and theoretical- legal method. In order to examine the evolution of the three systems the author used the historical and legal method. The paper concludes with highlight on diversity of available forms of support. The paper also includes the profile of functioning of the social security system, social provisions and social assistance not only in terms of their characteristics, but also in terms of the elements of subsidiarity.